THE STUDENTS’ ABILITY IN USING LEXICAL COLLOCATION IN SENTENCES AT STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA - Wulan Arianjani (XXXXXXXX, 2022)
Collocation is combinations of words that are collocate with each other so that the words produce the right meaning. There are two types of collocation, namely lexical collocation and grammatical collocation. There have been several previous studies which found that students have low ability to used collocation. The purpose of this research is to find out the students' ability in using lexical collocation in sentences at State Islamic University of North Sumatra in the English education department. The research focuses on the students' ability to use lexical collocation in simple sentences. This study used quantitative descriptive method to find out the students' ability. The sample of this study was 40 students in class TBI-1 semester 8. To collect the data the researcher gave a test to the students. The test results show that the minimum score was 33, the maximum score was 86, the mean score was 55.78, the median score was 53, the mode was 53, and the standard deviation is 13.42. Based on the test results, it was found that the 8th semester students majoring in English at the State Islamic University of North Sumatra were unable to use lexical collocation in sentences.Keywords: Collocation, Lexical collocation, Students’ ability.